(3hGHd GdfOG GdeNJUQ ef efGQ GdgOi aj HjGf Gdhba hGdGHJOGs - (3YHO Gddg Hf GdMGL eSYhO GdeZQHj GdeGdcj GdaGSjs; (3CMeO Hf YHO GdcQje Hf eMeO Hf YHO GdcQje GdGTehfj GdeGdcjs ((3Ydi Hf GdTjN eMeO GdCedjWj GdeGdcj s)
(3ChdgG (B:s
(3hHYO aEf GdbWH SjOj CMeO GdCTehfj GdeGdcj Ufa cJGHoG hSeGg efGQ GdgOi aj HjGf Gdhba hGdEHJOG s
(3BNQgG (B:s
(3hOdjdfG Edjc hEdi LfGJc LfGJ GdfYje eY GdPjf CfYeJ Ydjge hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdbQGAGJ hGdJLhjOs